An analysis of the law relating to insider trading in Malaysia / Nor Morina Hassan - Hassan, Nor Morina (Faculty of Law, 1987)
Insider trading is the term used to indicate the dealing in securities by person or persons (insiders) who by their relationship or connection with a Company are privy to confidential information regarding the Company which is likely to affect the price of its securities. The regulations against insider trading are directed not only to create a code of ethics^ for those favoured with confidential corporate information but also to preserve a fair market in securities. This is to ensure that all traders will have equal access for means to information about the securities traded.The policy which emphasive legislation regulating insider trading was clearly stated in a paper prepared in 1973 by the Department of Trade in the United Kingdom. Equality of means to information is very important because information is the only definite aspect of the security for which its worth can be measured. Since there is no obligation 3 or duty of the issuer to give a continuous flow of information, it is essential that any information which affects the value of the security is not only used by a section of the traders who have access to that information because of their relationship or connection with the company.